One-pot bottom-up synthesis of a 2D graphene derivative: application in biomolecular recognition and nanozyme activity. Issue 17 (10th August 2021) - Pandit, Subrata; De, Mrinmoy
Abstract : A facile synthesis of two-dimensional (2D) graphene like material through a bottom-up approach with controlled functionality and biological applications. Abstract : The synthesis of two-dimensional (2D) nanosheets such as graphene and its derivatives through a bottom-up approach has many advantages such as growth control and functionalization, but it is always challenging to get the desired material. Herein, we have reported the synthesis of water soluble 2D-nanosheets through a bottom-up approach from 2, 4, 6-tribromo-3-hydroxybenzoic acid via a self-coupling pathway and characterized them using several techniques. AFM and TEM analyses reveal that the synthesized material has a layered structure with a thickness of ∼1.2 nm. Also, the prepared nanosheets are amorphous in nature with high negative charge (−38 ± 2.5 mV). The flexible nature of 2D-nanosheets and their functionality can be used in many related applications. Therefore, we have utilized the synthesized 2D-nanosheets in biomolecular recognition studies. It was found that the enzymatic activity of α-chymotrypsin can be controlled reversibly in the presence of the synthesized 2D-nanosheets. The kinetic study revealed that the nanosheet surface selectively binds to the active sites of the enzyme through a competitive pathway. Furthermore, we explored the nanozyme activity of the material in a peroxidase-like activity assay of two bio-active molecules: Nicotinamide Adenine Dinucleotide Phosphate (NADH) and dopamine. The results suggest that the prepared material efficiently catalyzed the oxidation of NADH to biological cofactor NAD + and dopamine to aminochrome in the presence of H2 O2 . These synthesized graphene-like 2D-nanosheets with functional groups can be further tuned with other functionalities, which can open a new window for other related applications.